Kodiranje informacije o vrstnem redu v delovnem spominu - Dolenc, Barbara (Psihološka obzorja (Ljubljana), 2014)
Executive processes, such as coding for sequential order, are of extreme importance for higher-order cognitive tasks. One of the significant questions is, how order information is coded in working memory and what cognitive mechanisms and processes mediate it. The aim of this review paper is to summarize results of studies that explore whether order and item memory are two separable processes. Furthermore, we reviewed evidence for each of the proposed cognitive mechanism that might mediate order processing. Previous behavioural and neuroimaging data suggest different representation and processing of item and order information in working memory. Both information are maintained and recalled separately and this separation seems to hold for recognition as well as for recall. To explain the result of studies of order coding, numerous cognitive mechanisms were proposed. We focused on four different mechanisms by which order information might be coded and retrieved, namely inter-item associations, direct coding, hierarchical coding and magnitude coding. Each of the mechanisms can explain some of the aspect of order information coding, however none of them is able to explain all of the empirical findings. Due to its complex nature it is not surprising that a single mechanism has difficulties accounting for all the behavioral data and order memory may be more accurately characterized as the result of a set of mechanisms rather than a single one. Moreover, the findings beget a question of whether different types of memory for order information might exist.
Keywords: delovni spomin; working memory; procesiranje informacij; information processing; cognitive processes; kognitivni procesi; cognitive psychology; kognitivna psihologija